2005
DOI: 10.1007/s11173-005-0096-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Zn(II) and Cd(II) Complexes with Bisdithiophosphonates

Abstract: 2,4-Bis(4-methoxyphenyl)-1,3,2,4-dithiodiphosphetane-2,4-disulfide (Lawesson's reagent) reacts with stoichiometric equivalent of alkane diols HO(CH 2 ) n OH ( n = 2, 3, and 5) to form bisdithiophosphonic acid. The obtained crude bisdithiophosphonic acids are treated with dry NH 3 to give ammonium salts of bisdithiophosphonic acids. Ammonium salts of bisdithiophosphonic acids react with ZnSO 4 in water and Cd(Ac) 2 in ethanol to form new bisdithiophosphonate complexes of Zn(II) and Cd(II). The zinc and cadmium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…4 This category which includes dithiophosphonates and dithiophosphinate (scheme 1) are among well-known bidentate ligands and have been widely investigated. [5][6][7][8][9][10] The above mentioned biological and synthetic significance of dithiophosphonates derivatives prompted us to synthesize some dithiophosphonic acid ligands and their complexes. Previous studies have shown that the reaction of amines and alcohols with Lawesson reagent produces an ion pair and neutral ligand, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…4 This category which includes dithiophosphonates and dithiophosphinate (scheme 1) are among well-known bidentate ligands and have been widely investigated. [5][6][7][8][9][10] The above mentioned biological and synthetic significance of dithiophosphonates derivatives prompted us to synthesize some dithiophosphonic acid ligands and their complexes. Previous studies have shown that the reaction of amines and alcohols with Lawesson reagent produces an ion pair and neutral ligand, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Thiophosphorus species are an important class of S ‐donor ligands. This category, which includes dithiophosphonate, is among well‐known bidentate ligands, which have various applications in the agricultural and industrial fields as insecticides and nematicides . These compounds are also versatile ligands, displaying a broad variety of coordination patterns leading to a great diversity of molecular and supramolecular structures .…”
Section: Introductionmentioning
confidence: 99%